Corinthian Ignorance: Knowledge-Language and the Cultivation of Anxious Affects in 1 Corinthians - Zapata, Brigidda (Biblical interpretation, 2022)
The Corinthian assembly has been characterized by scholarship as full of anxieties that Paul writes to appease: anxieties about ritual impurity (1 Cor. 5:1–13), death (15:12–34), social relations (7:1–24), and other matters that occasion social conflict within the group. Paul, however, also writes in ways that evoke and fan anxiety, particularly through his appeals to knowledge. Knowledge is a central theme throughout 1 Corinthians, and in his use of knowledge-language Paul highlights a distinct lack or insufficiency in the knowledge of his audience. Mediated through the affective technology of the letter, the repeated impressions of unknowing, ignorance, and lack have the potential to coalesce in their audience into negative feelings around the threat of incurring shame. While Paul may rhetorically employ this language to position himself as a broker of right knowledge, the consequences of his rhetorical choices may emerge in his audience as a distinct set of anxious feelings read within the affective script of Roman verecundia.